Sustainable agricultural development paradigm formation in the context of managerial experience of industrialized countries - Nikitenko, Vitalina; Voronkova, Valentyna; Oleksenko, Roman; Matviienko, Halyna; Butkevych, Oksana (Journal of the University of Zulia, 2022)
The purpose of the article is to study the management experience of sustainable development of agriculture in the context of the paradigm of industrialized countries. To achieve the goal, general scientific and special-scientific methods of cognition were used, in particular, dialectical, formal-logical, analysis and synthesis, system-structural. This study analyzes the problems of "deep reform choice", which is the goal of creating an environmentally friendly society. The conditions under which agroecology restores and maintains the natural fertility of the land and contributes to the conservation of biodiversity, conserves soil and water resources, contributes to the achievement of high yields in the long term and opposes the use of agrochemicals are clarified. The management experience of industrialized countries (China, Japan, Malaysia), which, by developing agroecology, reproduce the natural flows of closed material cycles, resist emissions into the atmosphere, provide reliable access to land, water resources, information, credit and markets, advocates for a revision is being studied and generalizes legislation on property rights and support for farmers, investments in local infrastructure and agricultural products.